3D SURVEY IN COMPLEX ARCHAEOLOGICAL ENVIRONMENTS: AN APPROACH BY TERRESTRIAL LASER SCANNING - D. Ebolese; G. Dardanelli; M. Lo Brutto; R. Sciortino (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2018)
The survey of archaeological sites by appropriate geomatics technologies is an important research topic. In particular, the 3D survey by terrestrial laser scanning has become a common practice for 3D archaeological data collection. Even if terrestrial laser scanning survey is quite well established, due to the complexity of the most archaeological contexts, many issues can arise and make the survey more difficult. The aim of this work is to describe the methodology chosen for a terrestrial laser scanning survey in a complex archaeological environment according to the issues related to the particular structure of the site. The developed approach was used for the terrestrial laser scanning survey and documentation of a part of the archaeological site of Elaiussa Sebaste in Turkey. The proposed technical solutions have allowed providing an accurate and detailed 3D dataset of the study area. In addition, further products useful for archaeological analysis were also obtained from the 3D dataset of the study area.